Dimensions of cognitive reserve and their predictive power of cognitive performance and decline in the elderly - del Ser, Teodoro; Valeriano-Lorenzo, Elizabeth; Jáñez-Escalada, Luis; Ávila-Villanueva, Marina; Frades, Belén; Zea, María-Ascensión; Valentí, Meritxell; Zhang, Linda; Fernández-Blázquez, Miguel A. (Frontiers in Dementia, 2023)
Background. The relative importance of different components of cognitive reserve (CR), as well as their differences by gender, are poorly established. Objective. To explore several dimensions of CR, their differences by gender, and their effects on cognitive performance and trajectory in a cohort of older people without relevant psychiatric, neurologic or systemic conditions. Methods. Twenty one variables of education, occupation, social activities, and life habits of 1,093 home-dwelling and cognitively normal individuals, 68-86 years old, were explored with factorial analyses to delineate several dimensions of CR. These dimensions were contrasted with baseline cognitive performance, follow-up of their 5-year cognitive trajectory over , conversion to mild cognitive impairment (MCI) and brain volumes, by means of regression and growth curve models, controlling for gender, age, marital status, number of medications, trait anxiety, depression, and ApoE genotype. Results. Five highly intercorrelated dimensions of CR were identified with some differences by gender in their structure and effects. Three of them, “Education/occupation”, “Midlife cognitive activities” and “Leisure activities”, were significantly associated with late life cognitive performance accounting for more than 20% of its variance. “Education/occupation” significantly increased the rate of cognitive decline along the 5-year follow-up in individuals with final diagnosis of MCI but showed a risk reduction for MCI in men. None of these dimensions showed significant relations to grey or white matter volumes. Conclusions. Proxy markers of CR can be represented by five interrelated dimensions of CR. Education/occupation, Midlife cognitive activities and Leisure activities are associated with better cognitive performance in old age and provide a buffer against cognitive impairment. Education/occupation may delay the clinical onset of MCI and is also associated with the rate of change in cognitive performance.